(untitled) (Research, Society and Development, 2022)
Introduction: Over the years, orthodontic treatment in adult patients has become a reality. The modernization of orthodontic appliances with aesthetic and functional advantages justifies the increase in demand for treatment. This treatment sometimes must have a multidisciplinary approach aimed at eliminating the patient’s complaint and restoring occlusion, function and aesthetics, limiting itself to regions of the dental arch with some aesthetic or functional impairment. Finishing treatment with minimal periodontal loss at the end of treatment. Objective: To report a clinical case of orthodontic treatment in an adult patient for subsequent rehabilitation with implants and periodontal plastic surgery. Case report: Patient, female, 43 years old, sought orthodontic treatment complaining about her dental esthetics. Orthodontic treatment was chosen using a self-ligating esthetic ceramic Empower Clear DUAL system bracket (American Orthodontics, Sheboygan, WI, USA), and leveling was performed with expanded Tanzo nickel-titanium wires (American Orthodontics, Sheboygan, WI). , USA), 014”, .016”, .016” x .022” and .019” x .025” in the upper and lower arches, until reaching the .019”x.025” steel wires, with a slice in the second quadrant so that we can adjust the midline and gain space for later rehabilitation with implant in the region of element 13. Afterwards, we moved on to the phase of coordinating the arches and using intermaxillary elastics to assist in intercuspation. Final Considerations: The orthodontic treatment promoted the alignment and leveling of the teeth, restoring occlusion, aesthetics and function, allowing the correction of the midline and recovery of space for later rehabilitation of element 13.